Ferruginous bodies resolved by synchrotron XRF in a dog with peritoneal malignant mesothelioma. - Pascotto, Ernesto; Gianoncelli, Alessandra; Calligaro, Carla; Marcuzzo, Thomas; Melato, Mauro; Rizzardi, Clara; Pascolo, Lorella (Environ Sci Pollut Res Int, 2018)
Mesothelioma is a malignant tumor mainly correlated to occupational asbestos exposure. Rare reports describe its occurrence also in animals, mainly linked to asbestos in the environment. Asbestos exposure is demonstrated by the appearance of characteristic histological hallmarks: asbestos containing ferruginous bodies that are iron-based structures forming around fibers and also other dust particles. Here we present a clinical case of a suspect of mesothelioma in the peritoneum of a dog with parallel histological observation of ferruginous bodies. To possibly correlate the dog tumor to environmental exposure, we performed X-ray fluorescence (XRF) analyses at two different synchrotrons to resolve the ferruginous bodies' composition. While the histological examination diagnoses a tubulo-papillary mesothelioma, the XRF analyses show that ferruginous bodies contain Si particles, resembling formations of exogenous origin; however, the morphology is unlikely that of asbestos fibers. We speculate that the peritoneal mesothelioma of this dog could be related to environmental exposure to non-asbestos material.
Keywords: Animals; Asbestos; Dogs; Environmental Exposure; Immunohistochemistry; Iron; Lung; Lung Neoplasms; Male; Mesothelioma; Peritoneal Neoplasms; Silicon; Spectrometry, X-Ray Emission; Synchrotrons

Iron-related toxicity of single-walled carbon nanotubes and crocidolite fibres in human mesothelial cells investigated by Synchrotron XRF microscopy. - Cammisuli, Francesca; Giordani, Silvia; Gianoncelli, Alessandra; Rizzardi, Clara; Radillo, Lucia; Zweyer, Marina; Da Ros, Tatiana; Salomè, Murielle; Melato, Mauro; Pascolo, Lorella (Sci Rep, 2018)
Carbon nanotubes (CNTs) are promising products in industry and medicine, but there are several human health concerns since their fibrous structure resembles asbestos. The presence of transition metals, mainly iron, in the fibres seems also implicated in the pathogenetic mechanisms. To unravel the role of iron at mesothelial level, we compared the chemical changes induced in MeT-5A cells by the exposure to asbestos (crocidolite) or CNTs at different content of iron impurities (raw-SWCNTs, purified- and highly purified-SWCNTs). We applied synchrotron-based X-Ray Fluorescence (XRF) microscopy and soft X-ray imaging (absorption and phase contrast images) to monitor chemical and morphological changes of the exposed cells. In parallel, we performed a ferritin assay. X-ray microscopy imaging and XRF well localize the crocidolite fibres interacting with cells, as well as the damage-related morphological changes. Differently, CNTs presence could be only partially evinced by low energy XRF through carbon distribution and sometimes iron co-localisation. Compared to controls, the cells treated with raw-SWCNTs and crocidolite fibres showed a severe alteration of iron distribution and content, with concomitant stimulation of ferritin production. Interestingly, highly purified nanotubes did not altered iron metabolism. The data provide new insights for possible CNTs effects at mesothelial/pleural level in humans.
Keywords: Asbestos, Crocidolite; Cell Line; Epithelial Cells; Humans; Iron; Microscopy, Fluorescence; Nanotubes, Carbon

Puzzling Results from Germline Mutations Analysis in a Group of Asbestos-Exposed Patients in a High-risk Area of Northeast Italy. - Rizzardi, Clara; Athanasakis, Emmanouil; Cammisuli, Francesca; Monego, Simeone Dal; DE Spelorzi, Yeraldin Chiquinquira Castillo; Costantinides, Fulvio; Giudici, Fabiola; Pinamonti, Maurizio; Canzonieri, Vincenzo; Melato, Mauro; Pascolo, Lorella (Anticancer Res, 2017)
BACKGROUND: Germline mutations of the oncosuppressor gene breast cancer 1-associated protein 1 (BAP1) were recently related to an autosomal-dominant tumor predisposition syndrome (BAP1-TPDS), characterized by uveal melanoma, malignant mesothelioma (MM), cutaneous melanoma, and other malignancies. The demonstration that BAP1 mutations are strongly associated with MM has provided a real breakthrough in the study of genetic predisposition in MM, that may explain why only a fraction of asbestos-exposed individuals go on to develop MM. MATERIALS AND METHODS: To evaluate the possible role of BAP1 mutations in the epidemiology of sporadic MM, and their relationship with asbestos exposure, we determined the prevalence of germline BAP1 mutations by the Sanger method in a group of 29 asbestos-exposed patients, 21 of which were diagnosed with MM. They were residents of Trieste, a ship-building town in Northeast Italy with a very high incidence of mesothelioma. RESULTS: We identified non-obviously pathogenetic germline sequence variants of BAP1 in 3/29 patients and in 2/21 MM cases (10%). CONCLUSION: Non obviously pathogenic germline sequence variants of BAP1 were found. Nevertheless, limitations of predictive web tools allowed us to comment on some interesting peculiarities of our findings.
Keywords: Aged; Aged, 80 and over; Asbestos; Environmental Exposure; Female; Germ-Line Mutation; Humans; Italy; Lung Neoplasms; Male; Mesothelioma; Middle Aged; Risk; Tumor Suppressor Proteins; Ubiquitin Thiolesterase

Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al. (Toxicol Lett, 2016)
Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.

Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.

Peroxidase-like activity of ferruginous bodies isolated by exploiting their magnetic property. - Borelli, Violetta; Trevisan, Elisa; Vita, Francesca; Bottin, Cristina; Melato, Mauro; Rizzardi, Clara; Zabucchi, Giuliano (J Toxicol Environ Health A, 2012)
Ferruginous bodies (FB) are polymorphic structures whose formation is macrophage dependent, and are composed of a core, which may consist of an asbestos fiber coated with proteins, among which ferritin is the main component. Within ferritin, the ferric and ferrous ions are coordinated as ferrihydrite, which is the main iron (Fe) storage compound. However, when ferritin accumulates in some tissues following Fe overload it also contains magnetite along with ferrihydrite, which endows it with magnetic properties. Recently studies showed that magnetite exerts peroxidase-like activity, and since ferruginous bodies display magnetic properties, it was postulated that these particular structures may also contain magnetite within the ferritin coating, and thus may also exert peroxidase-like activity. Histochemical analysis for peroxidase of isolated FB smears demonstrated positive staining. Samples isolated from 4 different autopsy lung fragments were also able to oxidize 3,3',5,5'-tetramethyl-benzidine to a blue colored compound that absorbs at 655 nm. This activity was (1) azide and heat insensitive with optimal pH from 5 to 6, and (2) highly variable, changing more than 25-fold from one sample to another. These findings, together with evidence that the peroxidase-like activity of ferruginous bodies has a hydrogen peroxide and substrate requirement different from that of human myeloperoxidase, can exclude that this enzyme gives a significant contribution to the formation of FB. Standard Fe-rich asbestos fibers also express a peroxidase-like activity, but this appears negligible compared to that of ferruginous bodies. Strong acidification of standard Fe-containing asbestos fibers or magnetically isolated ferruginous bodies liberates a high amount of peroxidase-like activity, which is probably accounted for by the release of Fe ions. Further, FB also damage mesothelial cells in vitro. Data suggest that FB exert peroxidase-like activity and cytotoxic activity against mesothelial cells, and hence may be an important factor in pathogenesis of asbestos-related diseases.
Keywords: Air Pollutants, Occupational; Asbestos; Asbestosis; Benzidines; Catalysis; Cell Line; Chromogenic Compounds; Cytotoxins; Ferric Compounds; Ferritins; Ferrosoferric Oxide; Humans; Hydrogen-Ion Concentration; Lung; Magnetic Phenomena; Mesothelioma; Mineral Fibers; Oxidation-Reduction; Peroxidases; Respiratory Mucosa